Core strength as a paramount contributor for potential upper limb isometric strength - a correlational study - Kaur, H.; Chaudhary, S.; Chhabra, C. (Central European Journal of Sport Sciences and Medicine, 2023)
It is believed that a strong core will enable an athlete to effectively transfer forces from the lower extremities through the torso to the upper extremities. Control of the shoulder girdle force is important for the proper function of the upper extremities, although stabilising forces from the trunk and pelvis are also important. The purpose of this study is to determine the association between shoulder isometric push-up/pull-down strength and isometric strength of the abdominal muscles. Using the HUR Rehab-Line 5310 & 5120, isometric upper limb and core strength was measured. The statistical analysis revealed a moderate but significant positive association between the strength of the back muscles and isometric push-ups. Additionally, there was a weak and significant connection between isometric push-ups and abdominal strength. The study therefore draws the conclusion that there is a link between isometric upper limb performance and core musculature strength/stability. The abdominal and back muscles' isometric strength is closely tied to the isometric push-up, which is attributable to the contraction of the Pectoralis Major, Deltoid, and Triceps Brachii. The only muscle group identified to have a substantial and positive correlation with isometric pull-down strength is the abdominal muscles.